Individual and Combined Effects of Nanoplastics and Cadmium on the Rhizosphere Bacterial Community of Sedum alfredii Hance - Yixiu Wang; Hongyan Cheng; Yuenan Li; Ruiyan Ning; Yonghui Lv; Qing Wang; Haibo Zhang; Na Liu (Microorganisms, 2024)
Nanoplastics (NPs) and cadmium (Cd) coexist in soil, but the combined effects of NPs and Cd on the rhizosphere bacterial community remain unknown. In this study, high-throughput sequencing and PICRUSt2 functional analysis were employed to explore the individual and combined effects of polystyrene (PS) NPs (low concentration [N1, 100 mg·kg−1] and high concentration [N2, 1000 mg·kg−1]) and Cd (low concentration [C1, 0.6 mg·kg−1] and high concentration [C2, 4 mg·kg−1]) on the diversity, structural composition, and function of the rhizosphere bacterial community associated with Sedum alfredii Hance. Individually, PS NPs and Cd significantly reduced the soil pH, while the combined treatments induced a more significant decrease in pH. In contrast, combined PS NPs and Cd significantly increased the diethylenetriaminepentaacetic acid–Cd (DTPA-Cd) and total Cd concentrations. Compared with individual treatments, C2N2 significantly increased DPTA-Cd by 4.08%. N1 had no significant effect on the Chao1, observed species, or Shannon indices, while N2 significantly reduced the richness and diversity of the rhizosphere bacteria and altered their community structure. Furthermore, adding PS NPs exacerbated the effect of Cd on rhizosphere bacterial communities. Compared with individual Cd treatments, C2N2 significantly reduced the relative abundances of Actinobacteriota, Bacteroidota, Crenarchaeota, and Myxococcota by 19.76%, 2.01%, 1.49%, and 2.00%, respectively, and significantly increased the relative abundance of Acidobacteriota by 16.05%. A cluster heat map showed that the combined treatments attenuated glycan biosynthesis and metabolic function and enhanced the metabolism of cofactors and vitamins. These findings illuminate rhizosphere processes under co-contamination with heavy metals and PS NPs, supporting the practical application of phytoremediation to alleviate combined Cd and PS NP pollution.